'Zero tolerance' and drug education in Australian Schools - Munro, G.; Midford, Richard (T&F, 2001)
For a decade in Australia, drug education in schools has been shaped by the approach of harm minimization adopted by state and national governments alike. Harm minimization has been accepted broadly by drug educators, and has encouraged schools to deepen their commitment to drug education, allowed them to communicate honestly with students, and to respond to instances of drug use in a less confrontational and more caring manner. Despite those advances, the notion of 'zero tolerance' within schools has been promoted recently by protagonists in the formulation of drug policy and it is mentioned in the recently published national school drug education policy. This article suggests that the adoption of a zero tolerance policy will end the consensus among drug educators, reduce the efficacy of drug education, lead to more punitive treatment of youthful drug experimenters, while doing nothing to reduce drug use. It concludes the existing policy of harm minimization offers schools more scope to address drug issues in a constructive manner than does zero tolerance, which in practice may inflate the harmful effects on young people of drug use.